LEXICAL TRANSFORMATION OF BLENDER PART TERMS TRANSLATION IN THE USER MANUAL - Mukminin, Muhamad Saiful; Muhhit, Ahmad Abdul (ReALL - Research on Applied Linguistics and Literature, 2025)
This study aims to identify and describe lexical transformations in the translation of blender part terms from English to Indonesian in user manuals. Using a descriptive qualitative method with a product-based translation model, the data were drawn from 25 technical terms found in two bilingual Philips blender manuals (models HR2010 and HR2223). The data collection technique used was observation and note-taking, where terms were examined and recorded systematically. Data analysis was conducted using the Miles and Huberman model, involving data reduction, data display, and conclusion drawing. The results show five types of lexical transformation applied in the translation process: transposition, substitution, zero transformation, transposition + omission, and transposition + substitution. These transformations were used to adapt lexical forms and structures from the source language to the target language in ways that preserve meaning and enhance naturalness. Transposition helped adjust word order to fit Indonesian norms, while substitution provided more appropriate equivalents. Zero transformation applied when source terms had already been borrowed into Indonesian. The combinations of transformations aimed to ensure clarity, accuracy, and readability. This study implies that technical translation requires not only linguistic accuracy but also sensitivity to target language conventions. The findings contribute to translation practice by highlighting lexical transformations for translating technical terms effectively.